Advances on Sensitive Electron-Injection Based Cameras for Low-Flux, Short-Wave Infrared Applications - Fathipour, Vala; Bonakdar, Alireza; Mohseni, Hooman (Frontiers in Materials, 2016)
Short-wave infrared (SWIR) photon detection has become an essential technology in the modern world. Sensitive SWIR detector arrays with high pixel density, low noise levels and high signal-to-noise-ratios are highly desirable for a variety of applications including biophotonics, light detection and ranging, optical tomography, and astronomical imaging. As such many efforts in infrared detector research are directed towards improving the performance of the photon detectors operating in this wavelength range. We review the history, principle of operation, present status and possible future developments of a sensitive SWIR detector technology, which has demonstrated to be one of the most promising paths to high pixel density focal plane arrays for low flux applications. The so-called electron-injection (EI) detector was demonstrated for the first time (in 2007). It offers an overall system-level sensitivity enhancement compared to the p-i-n diode due to a stable internal avalanche-free gain. The amplification method is inherently low noise, and devices exhibit an excess noise of unity. The detector operates in linear-mode and requires only bias voltage of a few volts. The stable detector characteristics, makes formation of high yield large-format, and high pixel density focal plane arrays less challenging compared to other detector technologies such as avalanche photodetectors. Detector is based on the mature InP material system (InP/InAlAs/GaAsSb/InGaAs), and has a cutoff wavelength of 1700 nm. It takes advantage of a unique three-dimensional geometry and combines the efficiency of a large absorbing volume with the sensitivity of a low-dimensional switch (injector) to sense and amplify signals. Current devices provide high-speed response 5 ns rise time, and low jitter 12 ps at room temperature. The internal dark current density is 1 μA/cm2 at room temperature decreasing to 0.1 nA/cm2 at 160 K. EI detectors have been designed, fabricated, and tested during two generations of development and optimization cycles. We review our imager results using the first-generation detectors. In the second-generation devices, the dark current is reduced by two orders of magnitude, and bandwidth is improved by 4 orders of magnitude. The dark current density of the EI detector is shown to outperform the state-of-the-art technology, the